Microfocused ultrasound with visualization for face slimming: Preliminary results in four women - Bellote, Talitha Possagno Chaves; Miot, Helio Amante [UNESP] (Taylor & Francis, 2021)
Background: Microfocused ultrasound with visualization (MFU-V) is a recently developed technology that improves the laxity of the skin due to its capacity of precise focal heating of the dermis and deep layers, consequently inducing neocollagenesis and elastin remodeling. Purpose: This case series aimed to assess the efficacy of MFU-V in improving skin laxity, leading to the slimming of the lower third of the face in women who desired to naturally improve the shape of their faces. Patients and Methods: Four women between 29 and 36 years were submitted to a specific protocol with 4-MHz – 4.5-mm and 7-MHz – 3.0-mm transducers (Ulthera®) at the buccinators region in one session, and patients were evaluated after 180 days. GAIS (Global Aesthetic Improvement Scale) was assessed through standardized photographs (D0 vs D180). Results: All subjects perceived the slimming of the face after 180 days, as well as the improvement of skin laxity and contour. The practitioner and all the patients were highly satisfied with the results. The assessment of GAIS (D0 vs D180) resulted in score 3 (very improved) for three participants, and score 2 (improved) for one woman. All the patients classified pain experienced during the procedure as mild to moderate. Conclusion: We reported a technique that uses microfocused ultrasound with visualization leading to the slimming of the lower third of the face. Further systematic studies should be performed to understand the mechanism underneath the results and to maximize its performance.
Keywords: Collagen; Microfocused ultrasound; Neocollagenesis; Skin laxity; Ulthera®